Pengaruh Motivasi Belajar Terhadap Hasil Belajar Siswa Kelas 4 Sekolah Dasar - Rizki Zuliani; Adinda Nurfadiyah; Siti Selfiyana (Jurnal Pendidikan Sosial Dan Konseling, 2023)
In this technologically advanced and increasingly modern era, there are not a few students who have less than optimal learning outcomes in terms of cognitive, moral, and even ethical that students have which does not really describe a successful educational process. There are a number of students who drop out of school due to wrong associations, students who are morally corrupted, have no manners towards teachers or parents, do not speak kind words to other people and other cases that have occurred. For example, morally damaged children, such as skipping school, saying impolite words, dressing badly, stealing, slandering, bullying and so on. For this reason, education becomes learning outcomes as a reference or determinant of the success of the educator. The learning outcomes can affect student learning outcomes, one of which is student learning motivation. This motivation to learn is one of the important aspects or factors in the educational process, motivation to learn is a desire, ability, will that encourages someone to do something. Student motivation can be regarded as a critical level of success in achieving good learning outcomes. From several previous studies stated that this learning motivation has a very positive influence on student learning outcomes. From the results of the researchers' observations that in these schools the learning motivation of each child is different. It can be seen by behavior such as not attending on time when online learning takes place, not responding well when participating in the teaching and learning process taking place, collecting assignments at random or even past the specified collection time and other attitudes that illustrate the low motivation of student learning .From some of the descriptions above, the researcher raised a problem "The Influence of Learning Motivation on Learning Outcomes of Grade 4 Elementary School Students". It is hoped that this research will be useful for researchers, teachers, parents, students, and several other parties to gain knowledge and be able to pay attention and find ways so that students can have good learning motivation, by looking at and paying attention to these variables to improve learning outcomes for each child .